BUDAYA INTI, SIKAP BAHASA, DAN PEMBANGUNAN KARAKTER BANGSA: KASUS PENUTUR BAHASA-BAHASA DAERAH UTAMA DI INDONESIA - E. Aminudin Aziz (Masyarakat Linguistik Indonesia, 2013)
This article addresses three main issues in relation to culture’s core values, language attitude and maintenance, and character building. Using a theory previously developed by Smolicz and Secombe (1985), this study deviced instruments that enabled us to understand respondents’ perceptions about their culture’s core values. The respondents were recruited voluntarily from four major speakers of local languages in Indonesia, including speakers of Javanese, Sundanese, Minangnese, and Bataknese. They were given a set of questionnaires and when relevant were interviewed to further clarify their responses. The analyses found that each group viewed their culture’s core values differently, i.e. Javanese see language as their core cultures. Sundanese believe that a real Sundanese will stay in the Sundanese Land, embrace Islam, and speak in Sundanese. They also regard traditional music of kecapi suling and Cianjuran as the real Sundanese culture. On the other hand, Minang language speakers believed that it is the ability to appreciate — through making and tasting — traditional food that has made them true Minangnese. Meanwhile, it is strongly believed that you cannot become a true Bataknese until you know, feel, and fully understand the ways people of Batak origins speak, including tone, pitch, and intonation.